Anti-Obesity Activity Of Pandanus Amaryllifolius Roxb. And Vitex Negundo Linn. : Isolated Compounds With PTP1B Inhibitory Effects - Rathnasamy, Selestin (2022)
The role of protein tyrosine phosphatase 1B (PTP1B) as the negative modulator of leptin-mediated signaling, has made PTP1B an excellent target for obesity treatment. In spite of the enormous attempts, selective, effective, and safer PTP1B inhibitors are yet to be discovered. In this study, the effects of Pandanus amaryllifolius Roxb. (PA) and Vitex negundo Linn. (VN) on high calorie diet (HCD)-induced obesity were evaluated.